Alice in pornoland : hardcore encounters with the Victorian gothic - Marks, Laura Helen, 1981- (Feminist media studies (University of Illinois (System). Press), 2018)
"While pornographic film asserts itself as the rebellious cousin to the literary and cinematic canon, porn nonetheless relies on a particular 'Victorianness' in generating eroticism--a Gothic Victorianness that is monstrous and restrained, repressed but also perverse, static but also transformative, and preoccupied by gender and sexuality in both regressive and progressive ways. Pornographic films enthusiastically expose the perceived hypocrisy of this Victorianness, rhetorically equating it with mainstream, legitimate culture, as a way of staging pornography's alleged sexual authenticity and transgressive nature. By analyzing pornographic neo-Victorian adaptations of nineteenth century pornographic literature, Lewis Carroll's Alice books, Robert Louis Stevenson's Strange Case of Dr. Jekyll and Mr. Hyde, Oscar Wilde's The Picture of Dorian Gray, and Bram Stoker's Dracula, Laura Helen Marks argues that the rupture and rearticulation of social and corporeal propriety constitutes pornographic rhetoric. The predominantly American pornographic stories covered in the project appropriate canonical British icons as a method to refute the Old World framed as sexually repressed, yet hypocritical. In the process, these texts establish a postmodern American sexual identity framed as sexually liberated and culturally savvy. Porn adaptations expose the implicit pornographic aspects of 'legitimate' culture while also revealing the extent to which 'high' and 'low' genres rely on each other for self-definition and the attempted stabilization of the gendered sexual subject"--